A Quest for Freudian Eros in the Select Poems of Kamala Das - Deepa Caroline D, Anju C (International Journal of Advanced Science and Technology, 2019)
Sigmund Freud in his book Beyond the Pleasure Principle talks about the human mind, its metapsychological nature and its inclination towards pleasure and avoidance of pain. The book postulates that human existence is characterized by incessant conflict between Eros (life instinct) and Thanatos (Death instinct). The article analyzes the theme, ‘ideal love’ of Kamala Das, an Indian English poet, through a transposition of Freudian concept Eros to the selectlove poems of the poet. The article follows Das’ quest for ideal love until her final sublimation of it by finding a resort in spirituality. The article attempts to read love themes of Das’ select poems according to the arguments posited by Freud on life instincts, in the book Beyond the Pleasure Principle.